Salmonella Outer Protein B Suppresses Colitis Development via Protecting Cell From Necroptosis - Hu, Gui-Qiu; Yang, Yong-Jun; Qin, Xiao-Xia; Qi, Shuai; Zhang, Jie; Yu, Shui-Xing; Du, Chong-Tao; Chen, Wei (Frontiers in Cellular and Infection Microbiology, 2019)
Salmonella effectors translocated into epithelial cells contribute to the pathogenesis of infection. They mediate epithelial cell invasion and subsequent intracellular replication. However, their functions in vivo have not been well-identified. In this study, we uncovered a role for Salmonella outer protein B (SopB) in modulating necroptosis to facilitate bacteria escape epithelial cell and spread to systemic sites through a Salmonella-induced colitis model. Mice infected with SopB deleted strain ΔsopB displayed increased severity to colitis, reduced mucin expression and increased bacterial translocation. In vitro study, we found there was an increased goblet cell necroptosis following ΔsopB infection. Consistently, mice infected with ΔsopB had a strong upregulation of mixed lineage kinase domain-like (MLKL) phosphorylation. Deletion of MLKL rescued severity of tissue inflammatory, improved mucin2 expression and abolished the increased bacterial translocation in mice infected with ΔsopB. Intriguingly, the expression of sopB in LS174T cells was downregulated. The temporally regulated SopB expression potentially switched the role from epithelial cell invasion to bacterial transmission. Collectively, these results indicated a role for SopB in modulating the onset of necroptosis to increased bacteria pathogenesis and translocated to systemic sites.